1992
DOI: 10.1007/bf00304967
|View full text |Cite
|
Sign up to set email alerts
|

Rainfed mechanized farming and deforestation in central Sudan

Abstract: Sudan is threatened by a serious deforestation problem. Total forested area decreased by about 20 percent over the last two decades, largely as a result of the expansion of rainfed mechanized farming (RMF). To safeguard against the problems of deforestation, the government's Mechanized Farming Corporation requires each farmer to leave at least ten percent of the total farm area under shelterbelts. Few farmers pay attention to this clause. This paper addresses the problem of RMF expansion and analyzes the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Short-duration fallows are now becoming more appreciable, though short-duration fallows do normally not maintain a soil fertility at levels similar to those achieved with long periods of fallow (Aweto et al, 1992). However, wealthy farmers in regions of mechanized rainfed agriculture in Central Sudan can afford to buy many farms and shift among them as productivity decreases and abandoned farms can be recultivated after a period of time sufficiently long to allow for the restoration of soil fertility (Elnagheeb and Bromley, 1992). In contrast to the findings of the current study, Mustafa (2006) found that in the Gadarif region only 7 per cent of the farmers left a small part (less than 250 feddans) fallow.…”
Section: Re-improvement Of Land Productivitymentioning
confidence: 99%
“…Short-duration fallows are now becoming more appreciable, though short-duration fallows do normally not maintain a soil fertility at levels similar to those achieved with long periods of fallow (Aweto et al, 1992). However, wealthy farmers in regions of mechanized rainfed agriculture in Central Sudan can afford to buy many farms and shift among them as productivity decreases and abandoned farms can be recultivated after a period of time sufficiently long to allow for the restoration of soil fertility (Elnagheeb and Bromley, 1992). In contrast to the findings of the current study, Mustafa (2006) found that in the Gadarif region only 7 per cent of the farmers left a small part (less than 250 feddans) fallow.…”
Section: Re-improvement Of Land Productivitymentioning
confidence: 99%
“…Likewise, traditional smallholder farmers had their land expropriated to facilitate the establishment of the RMF schemes. The ensuing conflicts were frequent and serious (Elnagheeb and Bromley, 1992;Salih, 1992;Suliman, 1993;de Waal and Ajawin, 1995;Lane, 1998;Salam et al, 2002). Salih (1990) refers to the situation as a fight over shrinking land.…”
Section: Climate Change and Nomadic Migrationmentioning
confidence: 96%
“…Later, increased urbanization, partly induced by the civil war, perpetuated the demand for charcoal. In detailed accounts, Whitney (1987), af Ornas and Salih (1989), Ibrahim (1987), and Elnagheeb and Bromley (1992) show how the interaction of persistent drought, unsustainable land-use practices on the various farming schemes, high rates of human and livestock population growth, overgrazing, poor forest management practices, and perverse agricultural policies have all conspired to exacerbate deforestation.…”
Section: Climate Change and Nomadic Migrationmentioning
confidence: 98%
“…Autarky emerges (Bromley and Chavas, 1989). And the shrinking extensive margin (the shift from k ′ to k ∼) implies a gradual abandonment of agriculture (Elnagheeb and Bromley, 1992; 1994; Larson and Bromley, 1991).…”
Section: A Spatial Model Of Transport Corruptionmentioning
confidence: 99%